Nephrotic range of proteinuria in long standing rheumatoid arthritis: a diagnostic challenge - L. R., Srinivasa Guptha; Mohanasundaram, Kavitha; K. V., Rajalakshmi; Mohanan, Jagadeesan (International Journal of Advances in Medicine, 2023)
A 54-year-old male, a sero positive rheumatoid arthritis on treatment for 5 years, switched over to native drugs for 6 months. He was admitted with features suggestive of nephrotic range of proteinuria (Urine PCR- 8.32). A differential diagnosis of drug induced rheumatoid arthritis-amyloidosis was entertained. He underwent renal biopsy showed Membranous nephropathy (MN) (anti-phospholipase A2 receptor antibody PLA2R-positive). He was treated with high dose steroids, angiotensin receptor blockers and leflunomide as DMARD for rheumatoid arthritis. Nephrologist did not want to start mycophenolate mofetil/ rituximab since it was 1o MN. The proteinuria even after 1 month of steroids did not show any reduction; though anti-phospholipase A2 receptor antibody positive is a negative predictor for other secondary causes, considering his age and being a chronic smoker, we did a PET scan to rule out an internal malignancy. It revealed a metabolically active lesion in right upper lobe of the lung; Bronchoalveolar lavage (BAL) was done in that CBNAAT showed Mycobacterium tuberculosis positive. ATT was started and steroids tapered; a month into ATT, then Urine PCR reduced to 2 and at 3rd month of ATT, PCR was <1 and disease is under remission.